Modified Si-Miao Pill for Rheumatoid Arthritis: A Systematic Review and Meta-Analysis. (22nd May 2020) - Wang, Hui; Huang, Yao; Shen, Pan; Wang, Yu; Qin, Kai; Huang, Ying; Ba, Xin; Lin, Weiji; Chen, Zhe; Tu, Shenghao
Abstract : Objective . The aim of this review and meta-analysis was to assess the effects and safety of modified Si-Miao pill (mSMP) in treatment of rheumatoid arthritis. Design . A systematic literature search was carried out in eight databases from their available dates of inception to April 2020. After screening, fifteen randomized, controlled trials (RCTs) comparing the effects and safety of mSMP in combination with western medicine (including disease-modifying antirheumatic drugs (DMARDs) and nonsteroidal anti-inflammatory drugs (NSAIDs)) in treating rheumatoid arthritis patients were included after screening. Results . In comparison with DMARDs, or coadministration of DMARDs and NSAIDs, mSMP in combination with western medicine significantly lowered erythrocyte sedimentation rate (mean difference (MD) = -10.61, 95% confidence interval (CI) [−12.19, −9.03]), C-reactive protein (MD = −6.50, 95% CI [−8.43, −4.56]), rheumatoid factors (MD = −17.31, 95% CI [−24.34, −10.27]), swollen joint count (MD = −1.63, 95% CI [−2.29, −0.97]), tender joint count (MD = −1.98, 95% CI [−2.34, −1.62]), and morning stiffness time (MD = −24.37, 95% CI [−29.41, 19.33]) and ameliorated the condition of patients (odds ratio (OR) = 3.69, 95% CI [2.64, 5.14]). Additionally, mSMP in combination with western medicine seemed safer (OR = 0.49, 95% CI [0.30, 0.81]). Conclusion . The results of the meta-analysis study have shown that mSMP in combination with western medicine therapies appears to be more effective and safer than western medicine alone in the treatment of rheumatoid arthritis including reducing inflammatory markers and adverse events and improving symptoms. Howbeit, more high-grade, large-scale RCTs of mSMP in various countries and regions are still needed.